RISK AND CONSEQUENCE IN SUPPLY CHAIN IN ARAMCO COMPANY - Raneem E. Qari; Ahmed Attia (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Supply risk have multiple resources such as process, control, demand, supply and environment. In addition, supply risks are key challenges to supply chain management. The ability to identify these risks was the first step in managing risk. These risks had significantly negative impact on the supply chain. The study aimed to determine the risks and consequences that supply chain faces in Aramco Saudi Company. The need data had been collected based on online survey with 72 respondents. The first hypothesis in this study was test supply chain and susceptible in terms of supply chain risks. The second hypothesis was testing the relationship between the key drives of supply chain and risks. The third hypotheses was testing the relationship between the risks and internal supply chain. The fourth was test the impact of the external supply chain risks. The results shows that the acceptance of susceptible of supply chain risks. Outsourcing of supply chain and the product variants were the key drives supply chain which meant partly of hypothesis accepted, and there was a negative relationship between the risks and internal and external supply chain.